IMPLEMENTASI KEBIJAKAN PROGRAM SEKOLAH PENGGERAK DI SMP NEGERI 1 TEMANGGUNG - Joko Prasetyo; Nurkolis, Nurkolis; Muhammad Prayito (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of the School Driving Program (Program Sekolah Penggerak) as a national education policy aimed at improving school quality through the Merdeka Belajar framework. The research was conducted at SMP Negeri 1 Temanggung, one of the second cohort schools appointed to implement the program, which demonstrates strong institutional commitment and active involvement of driving teachers. The purpose of this study is to analyze how policy implementation is carried out in terms of communication, resources, disposition, and bureaucratic structure, based on the policy implementation model proposed by Edwards III. A qualitative descriptive approach was employed, with data collected through in-depth interviews, participatory observation, and document analysis. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation techniques. The findings indicate that the implementation of the School Driving Program at SMP Negeri 1 Temanggung has been carried out effectively and systematically. Policy communication is well established through participatory leadership and collaborative forums; human resources are strengthened through continuous professional development, learning communities, and intensive training; implementers demonstrate strong commitment and positive attitudes toward change; and bureaucratic structures are supported by clear standard operating procedures and coordination mechanisms. Moreover, the implementation of five key interventions consultative assistance, human resource development, differentiated learning, data-driven planning, and school digitalization has contributed to improvements in instructional practices and school performance. These results suggest that coherent policy implementation supported by strong leadership and collaborative culture can significantly enhance the effectiveness of educational reform at the school level.